Recognition of MR1-antigen complexes by TCR Vγ9Vδ2 - Loureiro, José Pedro; Vacchini, Alessandro; Berloffa, Giuliano; Devan, Jan; Schaefer, Verena; Nosi, Vladimir; Colombo, Rodrigo; Beshirova, Aisha; Montanelli, Giulia; Meyer, Benedikt; Sharpe, Timothy; Chancellor, Andrew; et al. (Frontiers in Immunology, 2025)
The TCR-mediated activation of T cells expressing the TCR Vγ9Vδ2 relies on an innate-like mechanism involving the butyrophilin 3A1, 3A2 and 2A1 molecules and phospho-antigens, without the participation of classical antigen-presenting molecules. Whether TCR Vγ9Vδ2 cells also recognize complexes composed of antigens and antigen-presenting molecules in an adaptive-like manner is unknown. Here, we identify MR1-autoreactive cells expressing the TCR Vγ9Vδ2. This MR1-restricted response is antigen- and CDR3δ-dependent and butyrophilin-independent. TCR gene transfer reconstitutes MR1-antigen recognition, and engineered TCR Vγ9Vδ2 tetramers interact with soluble MR1-antigen complexes in an antigen-dependent manner. These cells are present in healthy individuals with low frequency and are mostly CD8+ or CD4-CD8 double negative. We also describe a patient with autoimmune symptoms and TCR γδ lymphocytosis in which ~10% of circulating T cells are MR1-self-reactive and express a TCR Vγ9Vδ2. These cells release pro-inflammatory cytokines, suggesting a possible participation in disease pathogenesis. Thus, MR1-self-antigen complexes can interact with some TCRs Vγ9Vδ2, promoting full cell activation and potentially contributing to diseases.